PENGARUH PENGAWASAN TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR DINAS KEPENDUDUKAN CATATAN SIPIL KOLAKA UTARA - Jusmayanti, Jusmayanti; Muhammadiah, Muhammadiah; Fatmawati, Fatmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study is to determine the effect of supervision on the quality of public services in the office of population and civil Registry of North Kolaka  because Supervision is very important to evaluate  the employee’s work in repairing the less in the service. The number of sample in this study is 170 consiting of 80 employees and 90 communities The sample used is sample random sampling. Data collection techniques used questionnaires, observation and documentation.  Data analysis techniques used in the research are descriptive statistical analysis, correlation, and simple regression. Based on simple correlation and regression result of research in Capil Office showed the supervision has an effect on to public service quality at the Office of population and Civil Registration  of North Kolaka Regency. The supervision variable can give influence and have relationship with variable quality of public service at office of population and civil Regent of North Kolaka Regency.